2011
DOI: 10.1007/s11606-011-1949-5
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Follow-Up Test Results for Ambulatory Patients: A Systematic Review

Abstract: BACKGROUND: Serious lapses in patient care result from failure to follow-up test results. OBJECTIVE: To systematically review evidence quantifying the extent of failure to follow-up test results and the impact for ambulatory patients. DATA SOURCES: Medline, CINAHL, Embase, Inspec and the Cochrane Database were searched for Englishlanguage literature from 1995 to 2010. STUDY SELECTION: Studies which provided documented quantitative evidence of the number of tests not followed up for patients attending ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
150
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 70 publications
(227 reference statements)
1
150
0
1
Order By: Relevance
“…Poor communication and coordination between professionals and different elements of the health and social care system are the primary cause of many of the problems identifi ed (Dovey et al 2003 ). The lack of timely and accurate information after patients are discharged from hospital and delays in obtaining test results are both major risks (Kripalani et al 2007 ;Callen et al 2012 ). A more recent study of adverse events in primary care (ESPRIT) used a prospective method gathering data over seven consecutive days (Kret and Michel 2013 ).…”
Section: Error and Harm In Primary Carementioning
confidence: 99%
“…Poor communication and coordination between professionals and different elements of the health and social care system are the primary cause of many of the problems identifi ed (Dovey et al 2003 ). The lack of timely and accurate information after patients are discharged from hospital and delays in obtaining test results are both major risks (Kripalani et al 2007 ;Callen et al 2012 ). A more recent study of adverse events in primary care (ESPRIT) used a prospective method gathering data over seven consecutive days (Kret and Michel 2013 ).…”
Section: Error and Harm In Primary Carementioning
confidence: 99%
“…9,10 A systematic review by Callen et al found that, across 19 published studies, 6.8-62 % of lab tests were not followed up on. 11 It would not be an overstatement to conclude that the health care system lacks mechanisms for ensuring that test results are consistently conveyed to patients. 3,12 As appreciation of problems inherent in test result reporting processes has increased, a number of potential solutions have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The report urges that each of the stakeholders helps ensure that diagnostic information, as well as the ultimate diagnosis, is reliably communicated to the interested parties. This may be the 'low hanging fruit' that could jumpstart improvement, given how often failed communication of laboratory tests is cited as a contributing factor in diagnostic error [24,25]. Finally, the analytical phase of testing also has residual areas that demand attention in regard to timeliness and reliability, for example anatomic pathology [26] and all tests that depend on visual interpretation, point-of-care tests, and tests sent to reference laboratories [27].…”
mentioning
confidence: 99%